The entrepreneurs - Mitchum, Robert; Martin Sandler Productions (Washington, DC : PBS Video, 1987)
Profiles common threads among entrepreneurs and what motivated them to become successfull. Uses archival footage and interviews with great American businessmen and women
Copy available in DVD format
Keywords: Businessmen -- United States -- Biography; Women in business -- United States -- Biography; Entrepreneurship -- United States